1985
DOI: 10.2118/11900-pa
|View full text |Cite
|
Sign up to set email alerts
|

Fracturing Fluids: Fluid-Loss Measurements Under Dynamic Conditions

Abstract: When filter-cake-building additives are used in fracturing fluids, the commonly applied static, 30-minute API filtration test is unsatisfactory, because in a dynamic situation (like fracturing) the formation of a thick filter cake will be inhibited by the shearing forces of the fracturing fluid. A dynamic, filter-cake-controlled, leakoff coefficient that is dependent on the shear rate and shear stress at the fracture face is, therefore, introduced. A test apparatus has been constructed in which the fluid leako… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

1985
1985
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(17 citation statements)
references
References 4 publications
0
17
0
Order By: Relevance
“…14 Therefore, the C w data should be obtained with porous material representative of field conditions. Recent laboratory measurements 15 suggest that the filter cake is compressible at low pressure differentials and becomes incompressible at high D.p, contrary to the older data.…”
Section: The General Fluid Loss Modelmentioning
confidence: 61%
“…14 Therefore, the C w data should be obtained with porous material representative of field conditions. Recent laboratory measurements 15 suggest that the filter cake is compressible at low pressure differentials and becomes incompressible at high D.p, contrary to the older data.…”
Section: The General Fluid Loss Modelmentioning
confidence: 61%
“…Roodhart, [70] Navarette et al [59] and McGowen et al [61,62] demonstrated three stages for filter-cake buildup during a fracturing job when fracturing fluid flows perpendicular to the direction in which filter cake forms:…”
Section: Dynamic Fluid Lossmentioning
confidence: 99%
“…[61] Roodhart [70] and McGowen et al [61,62] Figure 39 Schematic picture of dynamic fluid loss process, Vitthal et al [61] Glenn at al. [30] classified the laboratory models designed by different researchers to measure the fluid loss dynamically into four groups:…”
Section: Dynamic Fluid Lossmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus the above description can be used to calculate in situ temperatures of e.g. crosslinked polymer gels, which are known not to follow a square root of time dependency under dynamic conditions(l4, 15). …”
Section: Temperature Recovery After Fracture Closure 'mentioning
confidence: 99%